2008
DOI: 10.1002/chin.200833035
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis, Antitubercular and Antimicrobial Activities of Some New Pyrazoline and Isoxazole Derivatives.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Compounds 1, 2, and 3 are acridone alkaloids; 4, 5, and 6 are sesquiterpenes, while 7 is a diterpenediol [5,37,85]. In Asia and America, several studies have reported pure compounds isolated from medicinal plants to have promising antimycobacterial activity [78,[115][116][117]. For example, Bisbenzylisoquinoline alkaloids from Tiliacora triandra (tiliacorinine, tiliacorine and 2′-nortiliacorinine) were found to have comparable antimycobacterial activity (MIC = 0.7-6.2 μg/ml) to the standard first line drugs against sensitive and resistant Mtb strains [108].…”
Section: Phytochemistry Of the Reported Plantsmentioning
confidence: 99%
“…Compounds 1, 2, and 3 are acridone alkaloids; 4, 5, and 6 are sesquiterpenes, while 7 is a diterpenediol [5,37,85]. In Asia and America, several studies have reported pure compounds isolated from medicinal plants to have promising antimycobacterial activity [78,[115][116][117]. For example, Bisbenzylisoquinoline alkaloids from Tiliacora triandra (tiliacorinine, tiliacorine and 2′-nortiliacorinine) were found to have comparable antimycobacterial activity (MIC = 0.7-6.2 μg/ml) to the standard first line drugs against sensitive and resistant Mtb strains [108].…”
Section: Phytochemistry Of the Reported Plantsmentioning
confidence: 99%